ChatGPT Translation Product Analysis in 'The Little Mermaid' - Utami, Ni Made Verayanti (Lingua Cultura, 2024)
This study aims to analyze the translation techniques used in the translation of the movie “The Little Mermaid” (2023) from English to Indonesian by ChatGPT. This research method uses a direct observation approach by collecting data from the Scraps From The Loft website, translating the text of the movie “The Little Mermaid” (2023) from English to Indonesian by using ChatGPT, and analyzing it through translation theory and thematic categories to see the accuracy and effectiveness of the translation. The data were collected from the movie dialog excerpts and their translations provided by ChatGPT. The analysis used the translation techniques proposed by Vinay and Darbelnet (2000), which include techniques such as borrowing, calque, literal translation, transposition, modulation, equivalence, and adaptation. The findings of this study show a diverse application of translation techniques, with the use of literal translation (48%), modulation, and adaptation (15%). Literal translation is often used due to its simplicity and straightforwardness, while modulation is used to adapt the translation to the nuances of Indonesian culture and language. In addition, adaptation was also noted especially in translating cultural references and idiomatic expressions to maintain the original meaning and context. The study concludes that ChatGPT effectively utilizes various translation techniques to produce coherent and coherent translations.